2020
DOI: 10.1155/2020/7018727
|View full text |Cite
|
Sign up to set email alerts
|

User Association Strategy for Energy Efficiency and Interference Mitigation of Heterogeneous Networks

Abstract: The necessity of the use of several mobile services increases every day. This requires the consumption of energy rates. Hence, minimizing the energy and interferences of mobile users are major concerns of Heterogeneous Networks (HetNet). This paper aims to improve the energy of mobile users by minimizing a weighted function. To consider significant weights values, we have exploited the multicriteria AHP method. The cost function represents the cost of users toward available BS. It includes the essential criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, when state-of-the-art methods failed to maintain the MUE's minimum necessary capacity due to significant co-tier and cross-tier interference, the suggested technique provided a minimum MUE capacity of 2 b/s/Hz, which is double the minimum required QoS threshold. In [145], the authors looked into energy-efficient UA and IM in 5G HetNets. They considered SINR, power usage, and user distance at the same time for UA and proposed a new algorithm which associated UEs with BSs based on their cost values.…”
Section: Combined Approaches For Rrm In 5g Hetnetsmentioning
confidence: 99%
“…Furthermore, when state-of-the-art methods failed to maintain the MUE's minimum necessary capacity due to significant co-tier and cross-tier interference, the suggested technique provided a minimum MUE capacity of 2 b/s/Hz, which is double the minimum required QoS threshold. In [145], the authors looked into energy-efficient UA and IM in 5G HetNets. They considered SINR, power usage, and user distance at the same time for UA and proposed a new algorithm which associated UEs with BSs based on their cost values.…”
Section: Combined Approaches For Rrm In 5g Hetnetsmentioning
confidence: 99%
“…After looking at the Table 1 and going through past literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] to the best of the author's knowledge, it is concluded that joint users association and EE maximization for effective radio resource management in HetNets with macro and small cells assisted by relays and D2D has not been explored in the past. The main contributions of the proposed work are summarized below:…”
Section: Motivation and Contributionsmentioning
confidence: 99%
“…The varying size of virtual resources can reduce the footprint of cloud users 26 . Reducing the energy usage and interference of mobile devices using a weighted factor in HetNets has been investigated in Achki et al 27 Overall total data rate has been maximized by allocating bandwidth to each user based on their requirements 28 . User association and resource allocation with decoupled access are explored in HetNets 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been multiple efforts from researcher to optimize the performance of SC HetNets in terms of reliability, coverage and capacity, throughput, and low complexity by mitigating the co-tier and cross-tier interferences since the last few years [15]- [25]. Most of the effective interference mitigation schemes are based on power control [15]- [19], user context information and load balancing among the network tiers by efficient user association [20]- [25]. Most of these schemes either handled only co-tier or cross-tier interference or could not provide the minimum required QoS and QoE to all users associated with different network tiers [5].…”
Section: Introductionmentioning
confidence: 99%